An abdominal surprise – A case report (Indian Journal of Case Reports, 2021)
Peritoneal loose bodies (PLBs), also known as peritoneal mice, are rare entity that is basically calcified pieces of necrotic tissue found in the peritoneal cavity. They are thought to evolve from torsion and separation of the appendices epiploicae, which are susceptible to such a process due to their narrow pedicle. We report the case of a 52-year-old male diagnosed as a case of chronic calculous cholecystitis. Workup investigations revealed nothing untoward other than gall stones. The patient was planned for laparoscopic cholecystectomy. Intraoperatively, a solitary smooth 6 cm × 6 cm spherical mass was found in the pelvic cavity not attached to any viscera or abdominal wall. The mass was diagnosed as a PLB. Such an entity is quite rare in medical literature and thus was sought for reporting.